2021
DOI: 10.3389/fpsyg.2021.751077
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Benefits of a Sport-Based Program for Female Cancer Survivors: The Role of Social Connections

Abstract: In the context of sports-based interventions for improving health and quality of life in chronic patients, participants could develop meaningful social relationships that affect their well-being as much as intervention activities. In this study, 80 female cancer survivors participated in a running-based group intervention (2 sessions/week; 1.5 h), while 51 acted as controls. The intervention lasted approximately 5 months. Unfortunately, the length of the intervention was reduced and sport activities were alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…Our findings support existing evidence demonstrating significant inverse associations between physical activity levels and psychological distress ( Stubbs et al, 2017 ; Wilke et al, 2021 ; Himbert et al, 2022 ) and suggest hematological cancer patients experiencing psychological distress are less inclined to engage in physical activity. In these patients, symptoms of psychological distress, such as lack of energy and motivation may lead to increased avoidance of physical activity ( Stults-Kolehmainen and Sinha, 2014 ; Stubbs et al, 2017 ; Durosini et al, 2021 ). It has been reported that COVID-19 related challenges, such as concerns about treatment delays, feelings of isolation, and increased financial hardship have contributed to heightened distress in cancer patients ( Zomerdijk et al, 2021a ; Beebe-Dimmer et al, 2022 ; Gates, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings support existing evidence demonstrating significant inverse associations between physical activity levels and psychological distress ( Stubbs et al, 2017 ; Wilke et al, 2021 ; Himbert et al, 2022 ) and suggest hematological cancer patients experiencing psychological distress are less inclined to engage in physical activity. In these patients, symptoms of psychological distress, such as lack of energy and motivation may lead to increased avoidance of physical activity ( Stults-Kolehmainen and Sinha, 2014 ; Stubbs et al, 2017 ; Durosini et al, 2021 ). It has been reported that COVID-19 related challenges, such as concerns about treatment delays, feelings of isolation, and increased financial hardship have contributed to heightened distress in cancer patients ( Zomerdijk et al, 2021a ; Beebe-Dimmer et al, 2022 ; Gates, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians can help by promoting community services that address the unique psychosocial challenges and needs within this population ( Leukaemia Foundation, 2022 ). Additionally, group-based exercise programs can serve as a meaningful avenue for patients to develop important social relationships that can improve their psychological wellbeing as much as the physical intervention activities itself ( Newton et al, 2020 ; Durosini et al, 2021 ). Remote, group-based exercise interventions can be considered for patients who remain isolated due to the risks posed by COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, social relationships increase empathy, understandable emotions and needs, and new friendships, which were also some of the main factors among participants’ take-home benefits. According to the literature, social connections, group support, and peer influence are important parts of an intervention that integrates physical and psychological aspects to promote quality of life [ 51 ]. In line with the literature, socio-relational opportunities played a relevant motivational role in participants’ engagement [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Group exercise oncology programs create opportunities to receive and provide SS and develop friendships with others who have cancer [ 1 , 9 ]. These programs bring together people who understand the cancer experience and provide the opportunity to share first-hand information [ 1 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, being around others with cancer may be difficult as it can draw attention to one’s own morbidity and mortality [ 1 , 11 ]. PA contexts can be a useful bridge between these benefits and challenges as many participants appreciate being able to talk about cancer if they want, but in a context where the focus is on a positive, healthy pursuit [ 1 , 9 ]. These programs can also normalize cancer and be a space where individuals do not need to explain they have cancer, are not treated as a patient or victim, and can talk openly and use dark humour that might make others uncomfortable in other settings [ 1 , 12 ].…”
Section: Introductionmentioning
confidence: 99%